Analisis Pemasaran Informasi Instagram @Glintsid Melalui 7P Marketing Mix - Panji Purnama Jati; Kusnandar Kusnandar; Tine Silvana (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Information as a service product has intangible characteristics, so it requires a more complex marketing strategy than physical products. This study aims to analyze digital information marketing strategies based on the 7P Marketing Mix theory (Product, Price, Place, Promotion, People, Process, Physical Evidence) on the Instagram account @glintsid. This study uses a qualitative descriptive method with a case study approach and data collection is carried out through observations of @glintsid's digital content, documentation of audience engagement, and literature studies. The results show that @glintsid implements the seven elements of the marketing mix in an integrated manner. The product element is realized through the provision of varied career and work skills education content; price is represented by non-financial sacrifices in the form of user time and attention; place is optimized through the use of Instagram distribution features; promotion focuses on increasing audience interaction and engagement; people include the role of the management team and management of two-way interactions with followers; process is reflected in the consistency of production flow and regular content distribution; and physical evidence is shown through the consistency of visual design and brand identity that builds account credibility. This study concludes that the implementation of the 7P Marketing Mix strategy through Instagram social media has proven effective in increasing information accessibility, expanding the reach of user engagement, and supporting job seekers' career literacy interactively.